(untitled) (Journal of Modern Mechanical Engineering and Technology, 2022)
Abstract: Three-dimensional (3D) printing is a flexible technique that has attracted increasing interest in recent years. 3D printing has powerful biodegradable materials that are important for environmental protection and emergencies such as COVID-19. To achieve better compatibility for customized and enhanced material characteristics, a variety of ways have been used. Companies and researchers are increasingly interested in biodegradable polymers and composites due to their easy production, eco-friendly, and suitability for a variety of applications. One small step toward protecting the world around us is the use of natural resources to produce fully or partially biodegradable composite materials. PHA (Polyhydroxyalkanoates), PLA (Polylacticacid), High impact polystyrene (HIPS), and PHB (Polyhydroxybutyrates) are examples of bioplastics that are produced and have similar functionality to conventional plastics while also being biodegradable. These materials have the potential to reduce our reliance on petroleum-based plastic, which may present environmental risks. Every country desperately needs to develop bioplastic usage and proper waste management for a pollution-free world. This review is expected to provide a general overview for 3D-printed biodegradable polymer and their applications using fused deposition modelling (FDM) technology.